Facile and green synthesis of fluorescent carbon dots from onion waste and their potential applications as sensor and multicolour imaging agents. Issue 34 (18th March 2016) - Bandi, Rajkumar; Gangapuram, Bhagavanth Reddy; Dadigala, Ramakrishna; Eslavath, Ravikumar; Singh, Surya S.; Guttena, Veerabhadram
Abstract : A novel, green approach for the synthesis of highly fluorescent carbon dots with 28% quantum yield by utilizing onion waste as precursor and employing a simple autoclave is reported, and applied them as Fe 3+ sensor & multi-coloured imaging agents. Abstract : Here, we report a novel, facile and green approach for the synthesis of highly fluorescent carbon dots (CDs) with 28% quantum yield by utilizing onion waste as a precursor and by employing a simple autoclave. Optical and physicochemical properties of as synthesized CDs were studied using transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), dynamic light scattering (DLS), X-ray diffraction (XRD), Raman, thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR), UV-visible, fluorescence spectroscopy and elemental analysis. These CDs exhibited high aqueous dispersibility, excitation dependent fluorescence emission and excellent stability to various effects like pH, high ionic strength and continuous irradiation. It was observed that the presence of Fe 3+ ions could result in a strong fluorescence quenching, hence these CDs were applied as a fluorescent probe for the selective & sensitive detection of Fe 3+ ions and a good linear correlation ( R 2 = 0.996) in the range of 0–20 μM with a detection limit of 0.31 μM was obtained. Cytotoxicity studies performed on both normal (HEK-293 cells) and cancerous (HeLa) cells revealed their excellent biocompatibility and they were further employed as fluorescent probes for multicoloured (blue, green and red) imaging of HeLa cells. Impressed by their high selectivity, photo stability and excellent biocompatibility, the Fe 3+ detection capability of these CDs was further evaluated in HeLa cells and applied for real water samples.